ANALISIS POJK No.1/POJK.07/2013 TERKAIT PERLINDUNGAN KONSUMEN DALAM ASPEK JASA KEUANGAN TERHADAP TELEMARKETING ASURANSI DI BNI LIFE SYARIAH - Sifak Saifuddin Ahmad; Abdul Mujib (Universitas Islam Negeri Mataram, 2023)
The digital era continues to develop following its times, this is no exception for insurance institutions at BNI Life Syari'ah. The presence of telemarketing innovation is proof that insurance at BNI Life Syari'ah has grown rapidly in cooperating with technology. This research is a type of literature research that utilizes essential and tertiary information dissected with a descriptive approach. The results of the research are first, the telemarketing strategy carried out by BNI Life Syari'ah is mostly in accordance with the regulations in the OJK because the practice has been considered according to the standards in the POJK, despite the fact that there are some things that are not in accordance with OJK rules no. 1 / POJK.07 / 2013, Second, there are still many statements from customers that they are often contacted by telemarketers outside working hours, So many customers feel upset. In accordance with the conclusions above, it is hoped that BNI Life Syari'ah can streamline its telemarketing strategy. In addition, more efforts are made to pay attention to the marketing point of view because this system will be considered bad if it is felt that many of the customers feel aggrieved and even deceived.